2009
DOI: 10.1177/1356766708100819
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing vacation packages through shop-at-home television programs: An analysis of consumers' consumption motives

Abstract: In most developed countries non-store retailing, especially shop-at-home television, has grown in importance and today's consumers have access to a wider and more diverse range of in-home shopping media than ever before. Not surprisingly non-store shopping behavior has increasingly been recognized as an important field of investigation. While previous research focused on shopper demographics and low-involvement products, relatively little is known about why consumers purchase products through shop-at-home tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…Lately, non-traditional media has been taken into account; such as the Internet, SNSs, and so forth [16,32,34,36]. Recent research found that people use technological media because of several motives, such as information seeking, entertainment, irritation, socialization, experience, and function [34,37]. Furthermore, tourism studies have adopted UGT to understand tourists' behavioral intention in various communication media.…”
Section: Motivations and Uses And Gratification Theorymentioning
confidence: 99%
“…Lately, non-traditional media has been taken into account; such as the Internet, SNSs, and so forth [16,32,34,36]. Recent research found that people use technological media because of several motives, such as information seeking, entertainment, irritation, socialization, experience, and function [34,37]. Furthermore, tourism studies have adopted UGT to understand tourists' behavioral intention in various communication media.…”
Section: Motivations and Uses And Gratification Theorymentioning
confidence: 99%
“…Moreover, although frequently nonhomogeneous and seemingly different, these efforts establish a new context for electronic commerce and practice as they implicate a variety of issues, such as global marketing, 24/7 operations, quick responses, competitive pricing, interactive search and navigation facilities, personalized and customized services, push and pull marketing mechanisms, etc. Inevitably, the travel and tourism industries have also faced new challenges that pushed them to adopt more innovative internetbased strategies and technologies (Connell and Reynolds, 1999;Hjalager, 2002;Palmer and McCole, 2000;Stockdale and Borovicka, 2006;Walsh and Gwinner, 2009;Werthner and Ricci, 2004;Yu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A korszerű értékesítési technológiák tárházában a televíziónak kezdetektől fogva meghatározó szerepe van. Egy képernyőre kerü-lő meggyőző prezentáció felkelti a nézők érdeklődését az adott termék iránt és fokozza vásárlási hajlandóságukat (Jenssen 1966;Skumanich, Kintsfather 1998;Walsh, Gwinner 2009). A tv-shopok prezentációi ugyan nélkülözik az interaktivitást, a sármos értékesítő mégis képes a személyes megszólítottság érzését kialakítani az otthon ülő tv-nézőben.…”
Section: Elméleti Háttérunclassified